Anti-proliferative Effects Curcumin in Human Acute Lymphoblastic leukemia Cell Line - Entezari, Maliheh; Khatamsaz, Sepideh; Dehghani, Hossein (Archives of Advances in Biosciences, 2017)
Acute lymphoblastic leukemia (ALL) is one of the most common cancers among children. Although there have been tremendous treatments, none of them have led to a precise cure. The use of herbal medicines which are safe and non-toxic have been demonstrated in this study. Curcumin is a polyphenol, hydrophobic product that is derived from turmeric plant. Curcumin has anti-toxic, anti-bacterial, anti-inflammatory, anti-cancer and anti-apoptosis properties. In recent years, extensive researches have been performed over the use of curcumin on cancers. In this study, CCRF-CEM cell line has been treated by curcumin. Rate of cytotoxicity of curcumin and the viability of the cells after treatment were evaluated by MTT assay and flow cytometry analysis. When different concentrations of curcumin were used upon the CCRF-CEM cell line at different times, it was found that curcumin effect depended on dose and time pattern. The results revealed that curcumin could induce apoptosis in CCRF-CEM cell line of acute lymphoblastic leukemia.